Cross‐Border Mergers and Upstreaming. (3rd September 2015) - Beladi, Hamid; Chakrabarti, Avik; Hollas, Daniel
Abstract: Global forces of fragmentation continue to distance (upstream) a product's conception from its end use. A concurrent flow of cross‐border mergers and upstreaming, by multinational corporations, dominates the fashion of doing international business. We investigate if there is any link between cross‐country variations in upstreaming within firms, apparent in international data, and mergers between firms across borders. Our empirical analysis reveals a significantly positive association between country upstreamness and cross‐border mergers. We build on Neary as well as Beladi et al. to provide a theoretical explanation of our findings in terms of the incentives in business strategic decision‐making to realise the gains from cross‐border mergers and upstreaming through the pricing mechanism of intermediate inputs in a vertically related oligopolistic industry.